The Reliability Analysis of Rotary Kiln A - Uli, Hotma; Ikhsan, Muhammad Rizky; Pratama, Setyo Yulio (International Journal of Education, Science, Technology, and Engineering (IJESTE), 2021)
Rotary Kiln as a pyroprocessing device is used to raise the temperature of the material to a high temperature (calcination) in a continuous process. By looking at the constraints on PT. Meratus Jaya Iron & Steel, whose production machines often have breakdowns, is a fundamental reason for researchers to increase the reliability level of PT. Meratus Jaya Iron & Steel. The research was conducted on the Rotary Kiln Machine made in Germany which plays a high enough role in the company. The method used is the Reliability with Mean Time to Repair Method (MTTR). From the results of calculations of Reliability with MTTR on Rotary Kiln A is Reliability at the time of 296 hours operation results obtained by 0.5371 and MTTR 537.7732. The higher the reliability value, the better the machine used in the operation process.